In Vitro Bacterial Activity of Seaweed (Kappaphycus alvarezii) Against Vibrio harveyi - Rukisah Rukisah; Rahmawati Rahmawati; Ricky Febrinaldy Simanjuntak (3BIO: Journal of Biological Science, Technology and Management, 2026)
Tiger shrimp (Penaeus monodon) is one of the featured products in Kalimantan Utara that still apply organic or traditional pond methods. Currently, production tiger shrimp has decreased due to a disease caused by Vibrio harveyi bacteria, which causes luminescent Vibrio disease or Vibriosis. Antibiotics are commonly used to treat this disease, but prolonged administration can lead to bacterial resistance The use of natural ingredients is an alternative solution to replace antibiotics, one of which is seaweed (Kappaphycus alvarezii). This study aims to determine the in-vitro inhibitory effect of seaweed extract against the growth of V. harveyi. This study using quantitative descriptive wih Kappaphycus alvarezii seeds from traditional farmers in Tarakan, Indonesia. Methods that were used in this research consisted of K. alvarezii extract preparation, bacteria preparation, phytochemical assay, and antibacterial assay of the extract followed by data analysis. The phytochemical assay consisted of alkaloid, phenol, flavonoid, saponin, and steroid assay. The antibacterial activity was evaluated using the paper disc diffusion method with seaweed extract concentrations of 5%, 10%, 15%, and 20%, while tetracycline served as the positive control and a solvent-only disc as the negative control. The results of phytochemical assay showed that the K. alvarezii extract contained alkaloid, phenol, flavonoid, saponin, and steroid. The antibacterial test showed that the seaweed extract with a concentration of 5% had an inhibition zone of 7 mm, 10% of 7.1 mm, 15% of 7.3 mm and at a concentration of 20% had the largest zone of inhibition with an inhibiton diameter of 13.3 mm. Based on these results, it can be concluded that the provision of Kappaphycus alvarezii is potentially inhibit the growth of V. harveyi in vitro but not significantly different when compared to the positive control. This activity is likely attributed to the natural compounds present in K. alvarezii, such as alkaloids, phenols, flavonoid, saponin, and steroids, which are known to possess antibacterial properties.